The International Arbitration Award as a Simple Proof Requirement in Bankruptcy - Rahayu Hartini; Hasani Moh. Ali; Mochammad Tanzil Multazam; Moh. Faizin; Ahmad Dzulfiqar Hibatullah Putra (Universitas Negeri Semarang, 2024)
Bankruptcy and Arbitration are forms of mechanisms for resolving disputes among parties. The purpose of this research is to explore the use of international arbitration awards as a simple proof requirement in bankruptcy cases. The research methods employed include the statute approach and conceptual approach. The findings of this research indicate that international arbitration awards can be admissible as simple proof due to the final and binding nature of international arbitration awards when they meet certain requirements established by Indonesian positive law. Specifically, if an international arbitration award has been registered and requested for enforcement at the Central Jakarta District Court, the international arbitration award is considered valid. Meeting these criteria, international arbitration awards, as authentic evidence, fulfill the simple proof requirement. However, if an international arbitration award does not meet these requirements, it cannot be considered authentic evidence in bankruptcy proceedings under Indonesian positive law, as the authenticity of international arbitration awards is only recognized when they have been registered and requested for enforcement.